Strengthening Early Childhood Empathy Character Through the Islamic-Themed Storytelling Method Assisted by the Interactive Flat Panel (IFP) - Adinda Ayu Pramita Sari; Siti Marli'ah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to describe the implementation of the Islamic-themed storytelling method assisted by the Interactive Flat Panel (IFP) in strengthening the empathy character of children aged 5–6 years at TK Islam Al-Jazilah Semanding Tuban. The study employed a qualitative approach using a case study design. The research subjects consisted of 16 children in Group B, the classroom teacher, the principal, and parents as supporting informants. Data were collected through observations, interviews, and documentation, and then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The trustworthiness of the data was ensured through source triangulation and technique triangulation. The findings indicate that the Islamic-themed storytelling method assisted by the IFP was implemented systematically through the selection of stories about the Prophets containing values of empathy, compassion, mutual assistance, and respect for others. The use of AI Prompt-based animated videos displayed through the IFP enhanced children's attention, enthusiasm, and engagement during the learning process. The children's empathy character developed across eight indicators, namely understanding the feelings of others, caring, compassion, tolerance, helping others, respecting others, social sensitivity, and the ability to share and avoid selfish behavior. Therefore, the Islamic-themed storytelling method assisted by the IFP can serve as an effective learning strategy to support the strengthening of empathy character in early childhood.